2022
DOI: 10.1002/ccd.30517
|View full text |Cite
|
Sign up to set email alerts
|

Impact of implantation technique on conduction disturbances for TAVR with the self‐expanding portico/navitor valve

Abstract: Background: Use of a right−left (R−L) cusp overlap view for transcatheter aortic valve replacement (TAVR) with self-expanding valves has recently been proposed aiming to reduce permanent pacemaker implantation (PPMI). An objective, datadriven explanation for this observation is missing.Aims: To assess the impact of different implantation techniques on the risk of PPMI following TAVR with the Portico/Navitor TM transcatheter heart valve (THV; Abbott).Methods: A TAVR-population treated with Portico/Navitor TM ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…Notably, while not-negligible, rates of permanent pacemaker implantation were reasonably low, especially in light of the patient risk profile (mean age of > 82 years, and features of frailty in almost 40% of patients). It is plausible that technical refinements, such as use of the right-left cusp overlap view for TAVI deployment, may further reduce this risk [ 30 ]. In addition, and in keeping with other pragmatic studies on patients undergoing TAVI, we found evidence of a constant accrual of adverse events well after the index procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, while not-negligible, rates of permanent pacemaker implantation were reasonably low, especially in light of the patient risk profile (mean age of > 82 years, and features of frailty in almost 40% of patients). It is plausible that technical refinements, such as use of the right-left cusp overlap view for TAVI deployment, may further reduce this risk [ 30 ]. In addition, and in keeping with other pragmatic studies on patients undergoing TAVI, we found evidence of a constant accrual of adverse events well after the index procedure.…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 ] Even if the COT was established for specific self-expandable valves due to their greater extension into the LVOT, it has already been shown how this technique might influence ID, PPI need, and haemodynamic performance using balloon-expandable and other devices. [ 22 , 23 ] However, according to current data, there is no evidence for a potentially increased risk of coronary obstruction or upward dislocations (pop-outs) with a higher ID (within appropriate limits).…”
Section: Membranous Septum Lengthmentioning
confidence: 94%
“…However, post-TAVI new-onset conduction disturbances and permanent pacemaker implantation (PPMI) are still common procedural complications [6]. Even though a patient-tailored pre-procedural planning together with optimized implantation techniques have been studied and conducted in most Heart Centers, the PPMI rate following TAVI remains a double-digit value, especially in TAVI using self-expanding THVs [7][8][9].…”
Section: Introductionmentioning
confidence: 99%